Sodium acetate carbon source water treatment agent for sewage treatment and preparation method thereof
By developing a multifunctional sodium acetate carbon source water treatment agent, the problem of single function when used as a carbon source is solved, and effective treatment of heavy metals and difficult-to-degrade COD is achieved, which is suitable for high-altitude wastewater treatment in areas and industrial wastewater.
Patent Information
- Application Number
- CN202510202472.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-24
AI Technical Summary
In the prior art, sodium acetate has a single function when used as a carbon source, and cannot effectively coordinate the treatment of heavy metals and difficult-to-degrade COD, and has poor results in high-altitude areas and industrial wastewater treatment.
Develop a sodium acetate carbon source water treatment agent to form a multifunctional water treatment agent by reasonably formulating sodium acetate, polybutylene succinate, low-temperature activator, microbial activator, heavy metal adsorbent and COD degrading agent. The treatment agent covers the multi-layer structure through electrostatic spraying and centrifugal spray drying technology to achieve the effects of sustained and rapid release.
This water treatment agent can not only quickly activate denitrifying bacteria and improve nitrogen removal efficiency, but also effectively adsorb heavy metals and degrade difficult COD. It is suitable for treatment of wastewater in high cold areas and industrial areas, and has low temperature adaptability and high stability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, in particular to a sodium acetate carbon source water treatment agent for sewage treatment and a preparation method thereof. Background Art
[0002] In the process of sewage treatment, sewage treatment agents with various functions are used, and carbon source is one of them. Carbon source can not only promote the growth and reproduction of microorganisms, but also provide carbon elements required for denitrification and denitrification for denitrifying bacteria, thereby accelerating the removal of pollutants by microorganisms.
[0003] Sodium acetate, also known as sodium acetate, is a water-soluble salt that can quickly dissolve in water, releasing acetate ions, providing a rapidly available carbon source for microorganisms. Good biodegradability. In addition, sodium acetate can be effectively degraded by a variety of microorganisms, especially in anaerobic digestion and aerobic reactions during sewage treatment. It serves as a carbon source to support the growth and reproduction of microorganisms and promote the removal of organic matter. In certain wastewater treatment processes (such as anaerobic ammonia oxidation), the addition of sodium acetate can improve the removal efficiency of nitrogen and phosphorus. By providing an additional carbon source, it can help form a more favorable microbial community and improve the removal of N and P. However, the role of sodium acetate is mainly focused on the denitrification function, and the removal of heavy metals (such as Pb 2+ , Cr(VI)) and refractory COD. And due to the single function of sodium acetate, it cannot meet the treatment needs of complex scenarios such as high-cold areas and industrial wastewater. Therefore, constructing a multifunctional, low-temperature adaptive, and high-stability carbon source system is an urgent problem that technicians in this field need to solve. Summary of the invention
[0004] In view of this, the present invention proposes a sodium acetate carbon source water treatment agent for sewage treatment and a preparation method thereof, aiming to solve the problem of single function when sodium acetate is used as a carbon source in the current technology.
[0005] In one aspect, the present invention provides a sodium acetate carbon source water treatment agent for sewage treatment, comprising the following raw materials in parts by weight:
[0006] 65-75 parts of sodium acetate, 7-12 parts of polybutylene succinate, 3-4 parts of low-temperature activator, 0.5-1 parts of microbial activator, 8-13 parts of heavy metal adsorbent, and 0.5-1 parts of COD degrader.
[0007] Preferably, the sodium acetate carbon source water treatment agent for sewage treatment comprises the following raw materials in parts by weight:
[0008] 68-72 parts of sodium acetate, 9-11 parts of polybutylene succinate, 3-4 parts of low-temperature activator, 0.5-1 part of microbial activator, 9-11 parts of heavy metal adsorbent, and 0.5-1 part of COD degrader.
[0009] Preferably, the particle size of the polybutylene succinate is 50-100 μm;
[0010] The low temperature activator includes one or more of potassium formate, betaine, and potassium thiocyanate;
[0011] The microbial activator includes: 2-pyridinecarboxylic acid.
[0012] Preferably, the heavy metal adsorbent comprises sulfur-doped mesoporous biochar and chlorine-intercalated magnesium-aluminum layered double hydroxide;
[0013] The specific surface area of the sulfur-doped mesoporous biochar is 1250±50m 2 / g, the mass content of sulfur in the sulfur-doped mesoporous biochar is 10-12%;
[0014] The mass ratio of the sulfur-doped mesoporous biochar to the chlorine-intercalated magnesium-aluminum layered double hydroxide is (5-8): (3-5).
[0015] Preferably, the method for preparing the sulfur-doped mesoporous biochar comprises the following preparation steps:
[0016] The rice husk is ground and then soaked in a hydrochloric acid solution to obtain pretreated rice husk powder;
[0017] In a nitrogen atmosphere, the pretreated rice husk powder is mixed with potassium hydroxide and carbonized to obtain carbonized rice husk powder;
[0018] Sulfiding under a sulfur-containing mixed gas to obtain the sulfur-doped mesoporous biochar;
[0019] The concentration of the hydrochloric acid solution is 0.1-0.2 mol / L, and the soaking time is 1-2 h;
[0020] The mass ratio of the pretreated rice husk powder to potassium hydroxide is 1:(2-4), the carbonization temperature is 750-850°C, and the carbonization time is 1-2h;
[0021] The sulfur-containing mixed gas includes hydrogen sulfide and nitrogen, the volume ratio of the hydrogen sulfide to the nitrogen is 1:(3-4), the sulfurization temperature is 600-650° C., and the sulfurization time is 1-2 hours.
[0022] Preferably, the preparation method of the chlorine-intercalated magnesium-aluminum layered double hydroxide comprises the following steps:
[0023] After mixing magnesium nitrate, aluminum nitrate and water, add sodium hydroxide salt solution, perform hydrothermal reaction, and filter;
[0024] The filter residue is immersed in a hydrochloric acid solution and dried to obtain the chlorine-intercalated magnesium-aluminum layered double hydroxide;
[0025] In the sodium hydroxide salt solution, the molar ratio of sodium hydroxide to sodium chloride is 0.4:(0.1-0.2);
[0026] The molar ratio of magnesium nitrate, aluminum nitrate and sodium hydroxide is (0.2-0.3):0.1:0.4;
[0027] The temperature of the hydrothermal reaction is 55-65°C, and the time of the hydrothermal reaction is 10-12h;
[0028] The concentration of the hydrochloric acid solution is 0.1-0.2 mol / L, and the immersion time is 20-40 min.
[0029] Preferably, the COD degradation agent includes nano zero-valent iron@biochar;
[0030] The nano zero-valent iron@biochar is a nano zero-valent iron loaded sulfur-doped mesoporous biochar material.
[0031] Preferably, the method for preparing the nano-zero-valent iron-loaded sulfur-doped mesoporous biochar material comprises the following steps:
[0032] The sulfur-doped mesoporous biochar is placed in a ferric chloride solution and subjected to ultrasound to obtain a mixed solution;
[0033] The mixed solution is subjected to a supercritical reduction reaction, and then passivated and dried to obtain the nano-zero-valent iron-loaded sulfur-doped mesoporous biochar;
[0034] The mass volume ratio of the sulfur-doped mesoporous biochar to the ferric chloride solution is 1 g: (15-25 mL), the concentration of the ferric chloride solution is 0.3-0.6 mol / L, and the ultrasonic time is 20-40 min;
[0035] The pressure of the supercritical reduction reaction is 20-25 MPa, and the time of the supercritical reduction reaction is 1-2 h;
[0036] The passivation process includes: washing the product obtained by the supercritical reduction reaction with an ethanol solution of polyvinyl pyrrolidone, wherein the mass concentration of the ethanol solution of polyvinyl pyrrolidone is 0.1%-0.2%.
[0037] On the other hand, the present invention also provides a method for preparing the sodium acetate carbon source water treatment agent for sewage treatment, comprising the following preparation steps:
[0038] (1) mixing polybutylene succinate, chlorine-intercalated magnesium aluminum layered double hydroxide and a low-temperature activator to obtain a first mixture, spraying a binder on the surface of the first mixture to obtain core particles;
[0039] (2) mixing the nano-zero-valent iron-loaded sulfur-doped mesoporous biochar material with 2-picolinic acid to obtain a second mixture, and using electrostatic spraying to coat the second mixture on the surface of the core particles to form a 50-80 μm functional layer;
[0040] (3) mixing sodium acetate with a low-temperature activator to obtain a third mixture, and coating the third mixture on the surface of the functional layer by centrifugal spray drying to obtain treatment agent particles;
[0041] (4) Immersing the treating agent particles in a glutaraldehyde solution to undergo a cross-linking reaction, and after the cross-linking reaction is completed, drying is performed to obtain the sodium acetate carbon source water treating agent.
[0042] Preferably, in step (1), the binder is a hydroxypropyl methylcellulose ethanol solution, and the mass concentration of the hydroxypropyl methylcellulose ethanol solution is 3%-6%;
[0043] The spraying temperature is -20~-15℃;
[0044] In step (2), the voltage of the electrostatic spray method is 20-25 kV, and the flow rate of the electrostatic spray method is 1-2 mL / min;
[0045] In step (3), the inlet temperature of the centrifugal spray drying is 30-40°C, and the outlet temperature of the centrifugal spray drying is 5-8°C; the mass ratio of the low-temperature activator in step (1) to the low-temperature activator in step (3) is (1-2): 1;
[0046] In step (4), the mass concentration of the glutaraldehyde solution is 0.3%-0.6%, the pH is 8-8.5, and the cross-linking reaction time is 8-12s.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] 1. The present invention provides a sodium acetate carbon source water treatment agent for sewage treatment, comprising the following raw materials in parts by weight: 65-75 parts of sodium acetate, 7-12 parts of polybutylene succinate, 3-4 parts of low-temperature activator, 0.5-1 parts of microbial activator, 8-13 parts of heavy metal adsorbent, and 0.5-1 parts of COD degradation agent. The present invention selects sodium acetate as the main carbon source, which can provide easily degradable organic carbon and quickly activate denitrifying bacteria. In addition, sodium acetate is hydrolyzed to generate acetic acid to maintain the weak alkaline environment required for denitrification. Polybutylene succinate has the effect of slow release of carbon source, and continuously releases succinic acid (C4H6O4) through ester bond hydrolysis, avoiding excessive proliferation of bacteria caused by instantaneous excess of carbon source. At the same time, the degradation product succinic acid can be used as an electron shuttle to improve the efficiency of denitrification electron transfer. The low-temperature activator ensures that the sodium acetate carbon source water treatment agent remains liquid at -20°C, improving low-temperature adaptability.
[0049] 2. The present invention further defines that the microbial activator includes 2-pyridine carboxylic acid, which can induce the expression of nirS and nosZ genes of denitrifying bacteria to increase the activity of nitrate reductase (NAR); and can also react with Cu 2+ / Zn 2+ Form stable complexes to reduce the biological toxicity of heavy metals.
[0050] 3. The present invention further defines that the heavy metal adsorbent includes sulfur-doped mesoporous biochar and chlorine-intercalated magnesium-aluminum layered double hydroxide. The -SH groups on the surface of sulfur-doped mesoporous biochar can react with Pb 2+ / Cd 2+ Specific binding improves the adsorption capacity of sodium acetate carbon source water treatment agent for heavy metals. ⁻ It exchanges with CrO4²⁻ to improve the removal capacity of Cr(VI), while releasing OH⁻ to maintain the pH between 7-8 and optimize the conditions of denitrification and heavy metal precipitation.
[0051] 4. The present invention further defines that the COD degradation agent includes nano zero-valent iron@biochar, and zero-valent iron can promote Fenton-like reaction through Fe 0 →Fe² + Release electrons to generate -OH free radicals (Fenton-like reaction), degrading difficult-to-degrade organic matter (such as benzene).
[0052] 5. The present invention also provides a method for preparing a sodium acetate carbon source water treatment agent for sewage treatment, comprising the following preparation steps: (1) mixing polybutylene succinate, chlorine-intercalated magnesium aluminum layered double hydroxide and a low-temperature activator to obtain a first mixture, spraying a binder on the surface of the first mixture to obtain core particles; (2) mixing nano zero-valent iron-loaded sulfur-doped mesoporous biochar material with 2-pyridine carboxylic acid to obtain a second mixture, using electrostatic spraying to coat the second mixture on the surface of the core particles to form a 50-80 μm functional layer; (3) mixing sodium acetate with a low-temperature activator to obtain a third mixture, and using centrifugal spray drying to coat the third mixture on the surface of the functional layer to obtain treatment agent particles; (4) immersing the treatment agent particles in a glutaraldehyde solution for cross-linking reaction, and drying after the cross-linking reaction is completed to obtain the sodium acetate carbon source water treatment agent. The present invention adopts supercritical reduction technology: realizing zero-valent iron in-situ reduction and pore precise loading. A gradient coating design is adopted. The inner core particles include polybutylene succinate, chlorine-intercalated magnesium aluminum layered double hydroxide and some low-temperature activators to achieve a sustained release effect. The outer core includes sodium acetate and some low-temperature activators, which have a rapid release effect. The middle functional layer includes nano-zero-valent iron-loaded sulfur-doped mesoporous biochar materials and 2-pyridine carboxylic acid, which can block the inhibition of heavy metals on the bacterial flora. Both the inner core particles and the outermost outer core contain low-temperature activators, which enable them to still have a high dissolution rate at -25°C. DETAILED DESCRIPTION
[0053] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] The present invention provides a sodium acetate carbon source water treatment agent for sewage treatment, comprising the following raw materials in parts by weight:
[0055] 65-75 parts of sodium acetate, 7-12 parts of polybutylene succinate, 3-4 parts of low-temperature activator, 0.5-1 parts of microbial activator, 8-13 parts of heavy metal adsorbent, and 0.5-1 parts of COD degrader.
[0056] In some embodiments of the present invention, the sodium acetate carbon source water treatment agent for sewage treatment comprises the following raw materials in parts by weight:
[0057] 68-72 parts of sodium acetate, 9-11 parts of polybutylene succinate, 3-4 parts of low-temperature activator, 0.5-1 part of microbial activator, 9-11 parts of heavy metal adsorbent, and 0.5-1 part of COD degrader.
[0058] In some embodiments of the present invention, the particle size of the polybutylene succinate is 50-100 μm;
[0059] The low temperature activator includes one or more of potassium formate, betaine, and potassium thiocyanate;
[0060] The microbial activator includes: 2-pyridinecarboxylic acid.
[0061] In some embodiments of the present invention, the heavy metal adsorbent includes sulfur-doped mesoporous biochar and chlorine-intercalated magnesium-aluminum layered double hydroxide;
[0062] The specific surface area of the sulfur-doped mesoporous biochar is 1250±50m 2 / g, the mass content of sulfur in the sulfur-doped mesoporous biochar is 10-12%;
[0063] The mass ratio of the sulfur-doped mesoporous biochar to the chlorine-intercalated magnesium-aluminum layered double hydroxide is (5-8): (3-5).
[0064] In some embodiments of the present invention, the method for preparing sulfur-doped mesoporous biochar comprises the following preparation steps:
[0065] The rice husk is ground and then soaked in a hydrochloric acid solution to obtain pretreated rice husk powder;
[0066] In a nitrogen atmosphere, the pretreated rice husk powder is mixed with potassium hydroxide and carbonized to obtain carbonized rice husk powder;
[0067] Sulfiding under a sulfur-containing mixed gas to obtain the sulfur-doped mesoporous biochar;
[0068] The concentration of the hydrochloric acid solution is 0.1-0.2 mol / L, and the soaking time is 1-2 h;
[0069] The mass ratio of the pretreated rice husk powder to potassium hydroxide is 1:(2-4), the carbonization temperature is 750-850°C, and the carbonization time is 1-2h;
[0070] The sulfur-containing mixed gas includes hydrogen sulfide and nitrogen, the volume ratio of the hydrogen sulfide to the nitrogen is 1:(3-4), the sulfurization temperature is 600-650° C., and the sulfurization time is 1-2 hours.
[0071] In some embodiments of the present invention, the method for preparing the chloride-intercalated magnesium-aluminum layered double hydroxide comprises the following steps:
[0072] After mixing magnesium nitrate, aluminum nitrate and water, add sodium hydroxide salt solution, perform hydrothermal reaction, and filter;
[0073] The filter residue is immersed in a hydrochloric acid solution and dried to obtain the chlorine-intercalated magnesium-aluminum layered double hydroxide;
[0074] In the sodium hydroxide salt solution, the molar ratio of sodium hydroxide to sodium chloride is 0.4:(0.1-0.2);
[0075] The molar ratio of magnesium nitrate, aluminum nitrate and sodium hydroxide is (0.2-0.3):0.1:0.4;
[0076] The temperature of the hydrothermal reaction is 55-65°C, and the time of the hydrothermal reaction is 10-12h;
[0077] The concentration of the hydrochloric acid solution is 0.1-0.2 mol / L, and the immersion time is 20-40 min.
[0078] In some embodiments of the present invention, the COD degradation agent includes nano zero-valent iron@biochar;
[0079] The nano zero-valent iron@biochar is a nano zero-valent iron loaded sulfur-doped mesoporous biochar material.
[0080] In some embodiments of the present invention, the method for preparing the nano zero-valent iron-loaded sulfur-doped mesoporous biochar material comprises the following steps:
[0081] The sulfur-doped mesoporous biochar is placed in a ferric chloride solution and subjected to ultrasound to obtain a mixed solution;
[0082] The mixed solution is subjected to a supercritical reduction reaction, and then passivated and dried to obtain the nano-zero-valent iron-loaded sulfur-doped mesoporous biochar;
[0083] The mass volume ratio of the sulfur-doped mesoporous biochar to the ferric chloride solution is 1 g: (15-25 mL), the concentration of the ferric chloride solution is 0.3-0.6 mol / L, and the ultrasonic time is 20-40 min;
[0084] The pressure of the supercritical reduction reaction is 20-25 MPa, and the time of the supercritical reduction reaction is 1-2 h;
[0085] The passivation process includes: washing the product obtained by the supercritical reduction reaction with an ethanol solution of polyvinyl pyrrolidone, wherein the mass concentration of the ethanol solution of polyvinyl pyrrolidone is 0.1%-0.2%.
[0086] The present invention also provides a method for preparing the sodium acetate carbon source water treatment agent for sewage treatment, comprising the following preparation steps:
[0087] (1) mixing polybutylene succinate, chlorine-intercalated magnesium aluminum layered double hydroxide and a low-temperature activator to obtain a first mixture, spraying a binder on the surface of the first mixture to obtain core particles;
[0088] (2) mixing the nano-zero-valent iron-loaded sulfur-doped mesoporous biochar material with 2-picolinic acid to obtain a second mixture, and using electrostatic spraying to coat the second mixture on the surface of the core particles to form a 50-80 μm functional layer;
[0089] (3) mixing sodium acetate with a low-temperature activator to obtain a third mixture, and coating the third mixture on the surface of the functional layer by centrifugal spray drying to obtain treatment agent particles;
[0090] (4) Immersing the treating agent particles in a glutaraldehyde solution to undergo a cross-linking reaction, and after the cross-linking reaction is completed, drying is performed to obtain the sodium acetate carbon source water treating agent.
[0091] In some embodiments of the present invention, in step (1), the binder is a hydroxypropyl methylcellulose ethanol solution, and the mass concentration of the hydroxypropyl methylcellulose ethanol solution is 3%-6%;
[0092] The spraying temperature is -20~-15℃;
[0093] In step (2), the voltage of the electrostatic spray method is 20-25 kV, and the flow rate of the electrostatic spray method is 1-2 mL / min;
[0094] In step (3), the inlet temperature of the centrifugal spray drying is 30-40°C, and the outlet temperature of the centrifugal spray drying is 5-8°C; the mass ratio of the low-temperature activator in step (1) to the low-temperature activator in step (3) is (1-2): 1;
[0095] In step (4), the mass concentration of the glutaraldehyde solution is 0.3%-0.6%, the pH is 8-8.5, and the cross-linking reaction time is 8-12s.
[0096] Example 1
[0097] A sodium acetate carbon source water treatment agent for sewage treatment, comprising the following raw materials in parts by weight:
[0098] 65 parts of sodium acetate, 7 parts of polybutylene succinate, 3 parts of potassium formate (low-temperature activator), 0.5 parts of 2-picolinic acid (microbial activator), 5 parts of sulfur-doped mesoporous biochar and 3 parts of chlorine-intercalated magnesium aluminum layered double hydroxide, 0.5 parts of nano zero-valent iron loaded sulfur-doped mesoporous biochar material (COD degrader).
[0099] The method for preparing sulfur-doped mesoporous biochar comprises the following steps:
[0100] The rice husk was ground and then soaked in a 0.2 mol / L hydrochloric acid solution for 1 hour to obtain pretreated rice husk powder;
[0101] In a nitrogen atmosphere, the pretreated rice husk powder was mixed with potassium hydroxide (the mass ratio of the pretreated rice husk powder to potassium hydroxide was 1:2), and carbonized at 750°C for 1 h to obtain carbonized rice husk powder;
[0102] The sulfur-doped mesoporous biochar is obtained by sulfurizing the biochar at 600° C. for 1 hour in a mixed gas of hydrogen sulfide and nitrogen (the volume ratio of hydrogen sulfide to nitrogen is 1:4).
[0103] The preparation method of the chlorine-intercalated magnesium-aluminum layered double hydroxide comprises the following steps:
[0104] After mixing magnesium nitrate, aluminum nitrate and water, add sodium hydroxide salt solution (the molar ratio of sodium hydroxide to sodium chloride is 0.4:0.1), hydrothermally react at a temperature of 55°C for 10 hours, and filter; wherein the molar ratio of magnesium nitrate, aluminum nitrate and sodium hydroxide is 0.2:0.1:0.4.
[0105] The filter residue is immersed in a 0.1 mol / L hydrochloric acid solution for 20 minutes and then dried to obtain the chlorine-intercalated magnesium aluminum layered double hydroxide.
[0106] The method for preparing nano-zero-valent iron-loaded sulfur-doped mesoporous biochar material comprises the following steps:
[0107] The sulfur-doped mesoporous biochar was placed in a 0.3 mol / L ferric chloride solution (the mass volume ratio of the sulfur-doped mesoporous biochar to the ferric chloride solution was 1 g: 25 mL), and ultrasonicated for 20 min to obtain a mixed solution;
[0108] The mixed solution was subjected to a supercritical reduction reaction at a pressure of 25 MPa for 1 hour, and the product obtained by the supercritical reduction reaction was then washed with an ethanol solution of polyvinyl pyrrolidone with a mass concentration of 0.1%, and dried to obtain the nano zero-valent iron-loaded sulfur-doped mesoporous biochar.
[0109] A method for preparing a sodium acetate carbon source water treatment agent for sewage treatment comprises the following preparation steps:
[0110] The polybutylene succinate, the chlorine-intercalated magnesium aluminum layered double hydroxide and the low-temperature activator are mixed to obtain a first mixture, and a 3% mass concentration of hydroxypropyl methylcellulose ethanol solution is sprayed on the surface of the first mixture at a spraying temperature of -20°C to obtain core particles;
[0111] (2) mixing the nano-zero-valent iron-loaded sulfur-doped mesoporous biochar material with 2-picolinic acid to obtain a second mixture, and using an electrostatic spraying method, wherein the voltage of the electrostatic spraying method is 20 kV and the flow rate is 1 mL / min, so that the second mixture is coated on the surface of the core particles to form a 40 μm functional layer;
[0112] (3) mixing sodium acetate with a low-temperature activator to obtain a third mixture, and coating the third mixture on the surface of the functional layer by centrifugal spray drying (the inlet temperature of the centrifugal spray drying is 30° C., and the outlet temperature of the centrifugal spray drying is 8° C.), thereby obtaining treatment agent particles;
[0113] (4) Immersing the treating agent particles in a glutaraldehyde solution with a pH of 8 and a mass concentration of 0.3%, and performing a cross-linking reaction for 10 seconds. After the cross-linking reaction is completed, drying is performed to obtain the sodium acetate carbon source water treating agent.
[0114] The mass ratio of the low-temperature activator in step (1) to the low-temperature activator in step (3) is 1:1.
[0115] Example 2
[0116] A sodium acetate carbon source water treatment agent for sewage treatment, comprising the following raw materials in parts by weight:
[0117] 60 parts of sodium acetate, 12 parts of polybutylene succinate, 4 parts of betaine (low-temperature activator), 0.5 parts of 2-picolinic acid (microbial activator), 6 parts of sulfur-doped mesoporous biochar and 4 parts of chlorine-intercalated magnesium aluminum layered double hydroxide, 0.5 parts of nano zero-valent iron loaded sulfur-doped mesoporous biochar material (COD degrader).
[0118] The method for preparing sulfur-doped mesoporous biochar comprises the following steps:
[0119] After grinding the rice husk, soak it in a 0.1 mol / L hydrochloric acid solution for 2 hours to obtain pretreated rice husk powder;
[0120] In a nitrogen atmosphere, the pretreated rice husk powder was mixed with potassium hydroxide (the mass ratio of the pretreated rice husk powder to potassium hydroxide was 1:4), and carbonized at 850°C for 1h to obtain carbonized rice husk powder;
[0121] The sulfur-doped mesoporous biochar is obtained by sulfurizing the mixture at 650° C. for 1 hour in a mixed gas of hydrogen sulfide and nitrogen (the volume ratio of hydrogen sulfide to nitrogen is 1:3).
[0122] The preparation method of the chlorine-intercalated magnesium-aluminum layered double hydroxide comprises the following steps:
[0123] After mixing magnesium nitrate, aluminum nitrate and water, add sodium hydroxide salt solution (the molar ratio of sodium hydroxide to sodium chloride is 0.4:0.2), hydrothermally react at a temperature of 65°C for 10 hours, and filter; wherein the molar ratio of magnesium nitrate, aluminum nitrate and sodium hydroxide is 0.3:0.1:0.4.
[0124] The filter residue is immersed in a 0.2 mol / L hydrochloric acid solution for 30 minutes and then dried to obtain the chlorine-intercalated magnesium-aluminum layered double hydroxide.
[0125] The method for preparing nano-zero-valent iron-loaded sulfur-doped mesoporous biochar material comprises the following steps:
[0126] The sulfur-doped mesoporous biochar was placed in a 0.6 mol / L ferric chloride solution (the mass volume ratio of the sulfur-doped mesoporous biochar to the ferric chloride solution was 1 g:15 mL), and ultrasonicated for 20 min to obtain a mixed solution;
[0127] The mixed solution was subjected to a supercritical reduction reaction at a pressure of 25 MPa for 1 hour, and the product obtained by the supercritical reduction reaction was then washed with an ethanol solution of polyvinyl pyrrolidone with a mass concentration of 0.2%, and dried to obtain the nano zero-valent iron-loaded sulfur-doped mesoporous biochar.
[0128] A method for preparing a sodium acetate carbon source water treatment agent for sewage treatment comprises the following preparation steps:
[0129] The polybutylene succinate, the chlorine-intercalated magnesium aluminum layered double hydroxide and the first portion of betaine are mixed to obtain a first mixture, and a 3% mass concentration hydroxypropyl methylcellulose ethanol solution is sprayed on the surface of the first mixture at a spraying temperature of -15°C to obtain core particles;
[0130] (2) mixing the nano-zero-valent iron-loaded sulfur-doped mesoporous biochar material with 2-picolinic acid to obtain a second mixture, and using an electrostatic spraying method, wherein the voltage of the electrostatic spraying method is 25 kV and the flow rate is 2 mL / min, so that the second mixture is coated on the surface of the core particles to form a 40 μm functional layer;
[0131] (3) mixing sodium acetate with the second portion of betaine to obtain a third mixture, and coating the third mixture on the surface of the functional layer by centrifugal spray drying (the inlet temperature of the centrifugal spray drying is 40° C., and the outlet temperature of the centrifugal spray drying is 5° C.), thereby obtaining treatment agent particles;
[0132] (4) Immersing the treating agent particles in a glutaraldehyde solution with a pH of 8 and a mass concentration of 0.3%, and performing a cross-linking reaction for 10 seconds. After the cross-linking reaction is completed, drying is performed to obtain the sodium acetate carbon source water treating agent.
[0133] The mass ratio of the low-temperature activator in step (1) to the low-temperature activator in step (3) is 1:1.
[0134] Example 3
[0135] It is basically the same as Example 1, except that the weight parts of sodium acetate are 75 parts, polybutylene succinate is 10 parts, potassium thiocyanate is 4 parts, 2-picolinic acid (microbial activator) is 1 part, sulfur-doped mesoporous biochar is 8 parts, chloride-intercalated magnesium aluminum layered double hydroxide is 5 parts, and nano zero-valent iron-loaded sulfur-doped mesoporous biochar material (COD degrader) is 1 part.
[0136] Among them, the preparation method of sulfur-doped mesoporous biochar, the preparation method of chlorine-intercalated magnesium-aluminum layered double hydroxide and the preparation method of nano zero-valent iron-loaded sulfur-doped mesoporous biochar material are the same.
[0137] The preparation method of the sodium acetate carbon source water treatment agent for sewage treatment comprises the following preparation steps:
[0138] The polybutylene succinate, the chlorine-intercalated magnesium aluminum layered double hydroxide and the first portion of potassium thiocyanate are mixed to obtain a first mixture, and a 3% mass concentration hydroxypropyl methylcellulose ethanol solution is sprayed on the surface of the first mixture at a spraying temperature of -18°C to obtain core particles;
[0139] (2) mixing the nano-zero-valent iron-loaded sulfur-doped mesoporous biochar material with 2-picolinic acid to obtain a second mixture, and using an electrostatic spraying method, wherein the voltage of the electrostatic spraying method is 22 kV and the flow rate is 1 mL / min, so that the second mixture is coated on the surface of the core particles to form a 50 μm functional layer;
[0140] (3) mixing sodium acetate with the second portion of potassium thiocyanate to obtain a third mixture, and coating the third mixture on the surface of the functional layer by centrifugal spray drying (the inlet temperature of the centrifugal spray drying is 35° C., and the outlet temperature of the centrifugal spray drying is 5° C.), thereby obtaining treatment agent particles;
[0141] (4) Immersing the treating agent particles in a glutaraldehyde solution with a pH of 8 and a mass concentration of 0.3%, and performing a cross-linking reaction for 10 seconds. After the cross-linking reaction is completed, drying is performed to obtain the sodium acetate carbon source water treating agent.
[0142] Test Case
[0143] The carbon source release rate, heavy metal adsorption capacity and low temperature stability of the sodium acetate carbon source water treatment agent prepared in Test Examples 1-3 are shown in Table 1.
[0144] Table 1 Test results of Examples 1-3
[0145]
[0146] Test method: The carbon source release rate was tested by dynamic dissolution test (25℃ / 4h), and the heavy metal adsorption capacity was tested by ICP-MS (Pb 2+ / Cd 2+ ), low temperature stability was tested using -20°C freeze / thaw cycles (5 times).
[0147] It can be seen from the data in Table 1 that the sodium acetate carbon source water treatment agent provided by the present invention has good heavy metal adsorption and low temperature stability and a suitable carbon source release rate.
[0148] The sodium acetate carbon source water treatment agent prepared in Example 1-3 was put into simulated wastewater to test its treatment effect. The test results are shown in Table 2.
[0149] Test conditions: water temperature 5°C (simulating winter high-cold areas); inlet pollutant concentration TN = 45mg / L, COD = 180mg / L (containing 20% difficult-to-degrade organic matter), Pb 2+ 8ppm, Cr(VI)6ppm).
[0150] Dosage: 80mg / L.
[0151] Table 2 Treatment effect test results of Examples 1-3
[0152]
[0153] It can be seen from the test results in Table 2 that the denitrification efficiency of the sodium acetate carbon source water treatment agent provided by the present invention is ≥95%, and at a low temperature (5°C), a relatively high heavy metal / COD removal rate is still maintained.
[0154] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A sodium acetate carbon source water treatment agent for sewage treatment, characterized in that: Contains the following raw materials in parts by weight: 65-75 parts of sodium acetate, 7-12 parts of polybutylene succinate, 3-4 parts of low-temperature activator, 0.5-1 parts of microbial activator, 8-13 parts of heavy metal adsorbent, and 0.5-1 parts of COD degrader.
2. A sodium acetate carbon source water treatment agent for sewage treatment according to claim 1, characterized in that, Contains the following raw materials in parts by weight: 68-72 parts of sodium acetate, 9-11 parts of polybutylene succinate, 3-4 parts of low-temperature activator, 0.5-1 part of microbial activator, 9-11 parts of heavy metal adsorbent, and 0.5-1 part of COD degrader.
3. A sodium acetate carbon source water treatment agent for sewage treatment according to claim 2, characterized in that, The particle size of the polybutylene succinate is 50-100 μm; The low temperature activator includes one or more of potassium formate, betaine, and potassium thiocyanate; The microbial activator includes 2-pyridinecarboxylic acid.
4. A sodium acetate carbon source water treatment agent for sewage treatment according to claim 2, characterized in that, The heavy metal adsorbent includes sulfur-doped mesoporous biochar and chlorine-intercalated magnesium-aluminum layered double hydroxide; The specific surface area of the sulfur-doped mesoporous biochar is 1250±50m 2 / g, the mass content of sulfur in the sulfur-doped mesoporous biochar is 10-12%; The mass ratio of the sulfur-doped mesoporous biochar to the chlorine-intercalated magnesium-aluminum layered double hydroxide is (5-8): (3-5).
5. A sodium acetate carbon source water treatment agent for sewage treatment according to claim 4, characterized in that, The method for preparing sulfur-doped mesoporous biochar comprises the following preparation steps: The rice husk is ground and then soaked in a hydrochloric acid solution to obtain pretreated rice husk powder; In a nitrogen atmosphere, the pretreated rice husk powder is mixed with potassium hydroxide and carbonized to obtain carbonized rice husk powder; Sulfiding under a sulfur-containing mixed gas to obtain the sulfur-doped mesoporous biochar; The concentration of the hydrochloric acid solution is 0.1-0.2 mol / L, and the soaking time is 1-2 h; The mass ratio of the pretreated rice husk powder to potassium hydroxide is 1:(2-4), the carbonization temperature is 750-850°C, and the carbonization time is 1-2h; The sulfur-containing mixed gas includes hydrogen sulfide and nitrogen, the volume ratio of the hydrogen sulfide to the nitrogen is 1:(3-4), the sulfurization temperature is 600-650° C., and the sulfurization time is 1-2 hours.
6. A sodium acetate carbon source water treatment agent for sewage treatment according to claim 4, characterized in that: The preparation method of the chlorine-intercalated magnesium-aluminum layered double hydroxide comprises the following steps: After mixing magnesium nitrate, aluminum nitrate and water, add sodium hydroxide salt solution, perform hydrothermal reaction, and filter; The filter residue is immersed in a hydrochloric acid solution and dried to obtain the chlorine-intercalated magnesium-aluminum layered double hydroxide; In the sodium hydroxide salt solution, the molar ratio of sodium hydroxide to sodium chloride is 0.4:(0.1-0.2); The molar ratio of magnesium nitrate, aluminum nitrate and sodium hydroxide is (0.2-0.3):0.1:0.4; The temperature of the hydrothermal reaction is 55-65°C, and the time of the hydrothermal reaction is 10-12h; The concentration of the hydrochloric acid solution is 0.1-0.2 mol / L, and the immersion time is 20-40 min.
7. A sodium acetate carbon source water treatment agent for sewage treatment according to claim 2, characterized in that: The COD degradation agent includes nano zero-valent iron@biochar; The nano zero-valent iron@biochar is a nano zero-valent iron loaded sulfur-doped mesoporous biochar material.
8. A sodium acetate carbon source water treatment agent for sewage treatment according to claim 7, characterized in that: The method for preparing the nano zero-valent iron-loaded sulfur-doped mesoporous biochar material comprises the following steps: The sulfur-doped mesoporous biochar is placed in a ferric chloride solution and subjected to ultrasound to obtain a mixed solution; The mixed solution is subjected to a supercritical reduction reaction, and then passivated and dried to obtain the nano-zero-valent iron-loaded sulfur-doped mesoporous biochar; The mass volume ratio of the sulfur-doped mesoporous biochar to the ferric chloride solution is 1 g: (15-25 mL), the concentration of the ferric chloride solution is 0.3-0.6 mol / L, and the ultrasonic time is 20-40 min; The pressure of the supercritical reduction reaction is 20-25 MPa, and the time of the supercritical reduction reaction is 1-2 h; The passivation process includes: washing the product obtained by the supercritical reduction reaction with an ethanol solution of polyvinyl pyrrolidone, wherein the mass concentration of the ethanol solution of polyvinyl pyrrolidone is 0.1%-0.2%.
9. A method for preparing a sodium acetate carbon source water treatment agent for sewage treatment according to any one of claims 1 to 8, characterized in that: The preparation steps include: (1) mixing polybutylene succinate, chlorine-intercalated magnesium aluminum layered double hydroxide and a low-temperature activator to obtain a first mixture, spraying a binder on the surface of the first mixture to obtain core particles; (2) mixing the nano-zero-valent iron-loaded sulfur-doped mesoporous biochar material with 2-picolinic acid to obtain a second mixture, and using electrostatic spraying to coat the second mixture on the surface of the core particles to form a 50-80 μm functional layer; (3) mixing sodium acetate with a low-temperature activator to obtain a third mixture, and coating the third mixture on the surface of the functional layer by centrifugal spray drying to obtain treatment agent particles; (4) Immersing the treating agent particles in a glutaraldehyde solution to undergo a cross-linking reaction, and after the cross-linking reaction is completed, drying is performed to obtain the sodium acetate carbon source water treating agent.
10. The method for preparing a sodium acetate carbon source water treatment agent for sewage treatment according to claim 9, characterized in that: In step (1), the binder is a hydroxypropyl methylcellulose ethanol solution, and the mass concentration of the hydroxypropyl methylcellulose ethanol solution is 3%-6%; The spraying temperature is -20~-15℃; In step (2), the voltage of the electrostatic spray method is 20-25 kV, and the flow rate of the electrostatic spray method is 1-2 mL / min; In step (3), the inlet temperature of the centrifugal spray drying is 30-40°C, and the outlet temperature of the centrifugal spray drying is 5-8°C; the mass ratio of the low-temperature activator in step (1) to the low-temperature activator in step (3) is (1-2): 1; In step (4), the mass concentration of the glutaraldehyde solution is 0.3%-0.6%, the pH is 8-8.5, and the cross-linking reaction time is 8-12s.
Citation Information
Patent Citations
Traditional Chinese medicine dreg charcoal adsorbent carrying vulcanization nano zero-valent iron and preparation method and application of adsorbent
CN109908863A
Solid carbon source for promoting low-temperature denitrification and preparation method and application thereof
CN110683639A
Sulfur-modified iron-nitrogen-carbon catalyst as well as preparation and application thereof
CN117399045A
The Signal Processing Method and Apparatus for Amplify-and-Forward Relay Assisted Communication Systems with Source-to-Destination Direct Link
KR102311166B1